EGFR L747P mutation in one lung adenocarcinoma patient responded to afatinib treatment: a case report - Zhou, Tong; Zhou, Xiaoyue; Li, Peng; Qi, Chuang; Ling, Yang (Journal of Thoracic Disease, 2018)
EGFR mutation is an important driving event in the development of non-small cell lung cancer (NSCLC), especially in pathologically diagnosed lung adenocarcinoma and non-smoking women in Asia (1). Compared with traditional platinum-containing chemotherapy, NSCLC patients with certain EGFR sensitive mutations showed higher clinical response to EGFR tyrosine kinase inhibitors (EGFR-TKIs), as confirmed by a series of phase III clinical trials, such as WJTOG3405, OPTIMAL, LUXLUNG6 and so on.